Assessment of Rational Drug Prescribing Pattern in Geriatric Patients in Hyderabad Metropolitan - Nandagopal, Anitha; Koneru, Anupama; Koneru, Anupama; Rahman, Arifa; Pasha, Md Khalid; Ali, Md Khaja Yaqub (Indian Journal of Pharmacy Practice)
Background: Polypharmacy and inappropriate prescriptions are prominent prescribing issues among geriatric patients. Beer’s criteria, Drug-Drug interaction of common OTC drugs and WHO essential drug lists have been developed to assist in the reduction of potentially inappropriate medications prescribed to geriatric patients. Objective: This study was carried out to find out the rational prescription of drugs in the geriatric patients and to also investigate Polypharmacy. Methodology: A retrospective study on rational drug prescribing pattern in geriatric patient was carried out using prescriptions issued to the geriatric patients, 65 years and above, attending the outpatient and inpatient department of various hospitals and clinics of Hyderabad. A total of 125 prescriptions were collected and analyzed by using Beer’s Criteria. Results: In this study we observed that almost all prescriptions were with polypharmacy. Only 3% of drugs were prescribed on generic names and remaining all is on brand names. 11 (13.75%) prescriptions had one or more potentially inappropriate medicines from Beer’s Criteria and in 9 (11.25%) prescriptions drug-drug interactions were ascertained according to drugdrug interactions of common OTC drugs. Conclusion: Prevalence of polypharmacy was high which is usually unavoidable in the geriatric patients. Extending clinical pharmacist services can significantly improve rational use of medicines in geriatric population.
Keywords: Geriatric population; Rational drug use; Essential drug list; Polypharmacy; Beer’s criteria